Company Financial Performance Before And During The Covid-19 Pandemic In Companies Listed On The Indonesia Stock Exchange - Rafif Setyo Nugroho; Payamta (Jurnal Mantik, 2022)
This study was conducted with the aim of analyzing the differences in the company's financial performance before and during the Covid-19 pandemic in all sectors of the JASICA classification companies listed on the Indonesia Stock Exchange. This research was conducted with a sample of 335 companies that are included in the Main Board listing category on the official website of the Indonesia Stock Exchange. The variables used in this study are sales growth, current ratio, asset turnover, return on assets and debt ratio. This study explains that the company's financial performance as measured by sales growth and current ratios has increased, while the company's financial performance as measured by asset turnover, return on assets and debt ratios has decreased.